ANIMATION AS AN EFFECTIVE TOOL FOR ENHANCING STUDENTS’ SPEAKING ABILITIES - Sain Assylay Bakytzhankyzy; Zhumabekova Galiya Baiskanovna (Foundations and Trends in Modern Learning, 2025)
The integration of animation into foreign language classrooms has transformed the way learners develop their speaking abilities. Speaking competence, encompassing pronunciation, fluency, interactive skills, vocabulary use, and discourse organization, is a critical component of overall language proficieincy. This study explores the role and effectiveness of animation-based activities in enhancing learners’ speaking abilities. Using a descriptive approach, both quantitative data from classroom-based tasks and qualitative feedback from learners were considered. Findings indicate that animation provides visually rich, emotionally engaging, and contextually meaningful input, which supports learners in producing spoken language more confidently and accurately. At the same time, challenges related to technological access, potential passivity during viewing, and the need for pedagogical scaffolding remain. Implications for educators and language learners are discussed